Making Use of ‘Rumah Belajar Portal’ to Improve Students’ Ability to Read Descriptive Texts at Grade VII of SMPN 31 Bengkulu Tengah - Putri Yanentha Istamia (Universitas Bengkulu, 2019)
Rumah Belajar Portal (RBP) is an alternative online media that was built by the Ministry of Education and culture (KEMDIKBUD) to provide content learning materials for teachers and students, RBP contains some feature but the researcher focused on Sumber Belajar and Kelas Maya feature.This researcher aimed to find out if the use of Rumah Belajar Portal could improve students’ reading comprehension abilities on descriptive text, to describe the students’ participations in the classroom activities, and to describe the students’ responses. The design was classroom action research, which was conducted in two cycles. The subject comprised the students at grade VII of SMPN 31 Bengkulu Tengah and consisted of 11 students. Qualitative and quantitative data were used. The instruments were reading comprehension test, observation checklist (field note) and interview. The result showed that RBP could improve the students’ abilities in reading descriptive text. The students who passed the minimum criterion of mastery (KKM passing grade ?70) improved from 18% in preliminary data to 45% at the end of cycle 1 and to 82% at the end of cycle 2. As for participation, the students were active and enthusiastic in asking and answering the question about the lesson in teaching and learning process. The students’ responses were positive. This shows that RBP was effective to be used in reading descriptive text.